2022
DOI: 10.1075/prag.16.4.02fuk
|View full text |Cite
|
Sign up to set email alerts
|

Resistance against being formulated as cultural other

Abstract: So-called traditional theories in second langauge acquisition (SLA) have been criticized for their neglect to examine interactional, social, and political aspects in language practices. The present study will illustrate exoticization, one of the political phenomena observed in interactions between native-speaker and non-native speaker (NS/NNS). Exoticization is known as a covert power exercise where ‘self’ creates inferior ‘other’ in order to establish and maintain its superiority (Said 1978), which involves i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…Although in some cultures eating dogs and scorpions may be equally normative practices, by moving from domesticated to dangerous animals, Sky upgrades his supposition that Koreans eat 'unusual' things. This is similar to the phenomena observed by Fukuda (2006), in which cultural 'Others', and their cultural practices, are exoticised, exaggerated and stereotyped.…”
Section: A Brandt and C Jenkssupporting
confidence: 77%
See 2 more Smart Citations
“…Although in some cultures eating dogs and scorpions may be equally normative practices, by moving from domesticated to dangerous animals, Sky upgrades his supposition that Koreans eat 'unusual' things. This is similar to the phenomena observed by Fukuda (2006), in which cultural 'Others', and their cultural practices, are exoticised, exaggerated and stereotyped.…”
Section: A Brandt and C Jenkssupporting
confidence: 77%
“…For example, Fukuda (2006) suggests that the 'Otherisation' which occurs in her data is, in part, manifest in the assumptions made about aspects of Chinese national culture, such as low salaries, lack of industry and the lack of freedom to travel. She argues that such stereotyping and exoticising demonstrate how ideological positions can, intentionally or otherwise, be portrayed through social discourse, and that this can be interpreted as the exertion of power.…”
Section: Interculturality: National Cultural Differences and Identitimentioning
confidence: 95%
See 1 more Smart Citation
“…She finds that the construction of interculturality is achieved collaboratively, often as teams. Fukuda (2006) following this line of inquiry examining the exoticization of the "other," or foreigner in the interaction. Her findings show that participants may show resistance to the categorization of the other.…”
Section: Intercultural Talk and Conversationmentioning
confidence: 98%
“…This tradition is interested in the intersentential level of interaction and how participants' emic perspective is made known in talk. In more recent years, intercultural membership and identity construction has also been explored from a microanalysis of conversation utilizing conversation analysis techniques (Brandt & Jenks, 2011;Fukuda, 2006Fukuda, , 2008Higgins, 2007;Ikeda, 2008;Kim, 2008;Mori, 2003;Nishizaka, 1995Nishizaka, , 1999Zimmerman, 2007aZimmerman, , 2007bZimmerman, , 2009Zimmerman, , 2010aZimmerman, , 2010bZimmerman, , 2011. This line of inquiry has demonstrated that researchers can access how participants construct their perspectives and identities within conversation to perform various conversational actions within the discourse.…”
Section: Intercultural Talk and Conversationmentioning
confidence: 99%